REGIONAL AIRPORTS (Perner's Contacts, 2018)
The consequence of social and economic changes in the Czech Republic was the liberalization of air transport. After the politically bipolar Europe ceased to exist and the Czech Republic joined NATO, there was no need to keep so many military airports, which were therefore converted into civilian airports. After some time and especially recently, it is thought that the airports should be deemed as an integral part of the public transport infrastructure.